Prenatal breastfeeding education (PBE) and breastfeeding counseling (BC) influence the prenatal exclusive breastfeeding (EBF) preparation - Wahyuni, Sri; Prabandari, Yayi Suryo; Julia, Madarina; Hakimi, Mohammad (Basic and Applied Nursing Research Journal, 2023)
Introduction: Pregnant women frequently exhibit varied behaviors, such as having a lot of questions, showing insecurity, and fear. Objective: Pregnant women frequently exhibit varied behaviors, such as having a lot of questions, showing insecurity, and fear. As a result, their sensitivity and susceptibility to social expectations surrounding their capacity to breastfeed are increased. This study aims to assess the different knowledge and skills of breastfeeding counseling (BC) on health personnel, and to assess differences in intent, knowledge, prenatal self-efficacy, and prenatal professional support in third-trimester pregnant women. Methods: The study was randomized by applying a pre-test and post-test design in the health worker group and the post-test only control group in the group of pregnant women. A comparative test was done by comparing the intervention indicator between the treatment group and control group using t-test, one-way ANOVA, post hoc test, and chi-square test at a 95% significance level (p < 0.05). Results: There was a difference in the mean score of EBF knowledge, 26.85 95% CI (19.94–33.76) and BC skills, 13.17 95% CI (25.85–36.48) health workers at post-test and pre-test. The comparison of intergroup relations between pregnant women group with EBF intention in Group A, OR 6.83 95% CI (4.10–11.36), and in Group B, OR 1.86 95% CI (1.15–3.01), to the control group. Conclusion: There is a difference in intention, mean breastfeeding knowledge score, prenatal self-efficacy, and support of prenatal breastfeeding preparation between groups of third-trimester pregnant women.